Isolation and characterization of sulphate reducing bacteria from goat rumen and its inclusion to improve in vitro feed fermentation - UNIYAL, SANDEEP; CHAUDHARY, LAL CHAND; KALA, ANJU; AGARWAL, NEETA (The Indian Journal of Animal Sciences, 2022)
In the present study sulphate-reducing bacteria (SRB) were isolated from the rumen of goats fed a diet of wheat straw and concentrate in 50:50 ratio using specific medium followed by phenotypic and phylogenetic characterization. Based on the biochemical characteristics, four best SRB isolates were evaluated for their efficacy to reduce in vitro CH4 production and stimulate fibre digestion. It was found that true dry matter digestibility (IVTD) and production of metabolites were higher but methane emission was low by inclusion of live culture of SRB4 isolate as compared to control. Sequencing of 16S rDNA revealed 99% homology of SRB4 with Streptococcus caviae strain NR156902. The isolate also exhibited expression of dissimilatory sulphite reductase gene (dsR) gene substantiating sulphate reducing ability of the isolate. The results indicate the ability of SRB4 to reduce in vitro CH4 emissions and improve fibre digestibility, hence can be explored as an effective candidate for microbial feed additive to modify rumen fermentation, so that enteric methane production can be controlled.